Linear BVPs and SIEs for Generalized Regular Functions in Clifford Analysis. (8th May 2018) - Li, Pingrun; Cao, Lixia
Abstract : We study some properties of a regular function in Clifford analysis and generalize Liouville theorem and Plemelj formula with values in Clifford algebraA n ( R ) . By means of the classical Riemann boundary value problem and of the theory of a regular function, we discuss some boundary value problems and singular integral equations in Clifford analysis and obtain the explicit solutions and the conditions of solvability. Thus, the results in this paper will be of great significance for the study of improving and developing complex analysis, integral equation, and boundary value theory.